LEVEL BERPIKIR SISWA SMP BERGAYA KOGNITIF REFLEKSIF DAN IMPULSIFMENURUT TEORI VAN HIELE PADA MATERI SEGITIGA - Hazmin Sholiha Amimah; Harina Fitriyani (Universitas Muhammadiyah Semarang, 2017)
Geometry is a branch of mathematics that many applications in everyday life, but thestudent’s understanding of geometry tend to be low. Understanding the conceptof geometry put forward the process of geometric thinking. In Van Hiele's theory,geometric thinking is formulated into five levels of thinking that is level 0 (visualization), level 1 (analysis), level 2 (informal deduction), level 3 (deduction),and level 4 (rigor). This study aims to determine which level of student thinkingbased on Van Hiele theory in terms of reflective-impulsive cognitive style.Thisresearch is descriptive qualitative research. The subjects of the study were thestudents of class VIII E SMP Negeri 4 Yogyakarta consisting of two students ofreflective cognitive style and 3 students of cognitive impulsive style. Techniques ofcollecting data used tests (TLB) and interviews. Research instruments include MFFT to map students 'cognitive and TLB styles to determine students' level of thinking.Data analysis using Milles and Hubermanmodel.The results showed that thestudents' cognitive style tendency was dominated by reflective and impulsivecognitive style that was 69,69%. Based on TLB's written results and interviews show that the reflective or impulsive subjects are at level 2 (informal deduction). This suggests that the different of cognitive style do not cause differences in thinking levels based on Van Hiele's theory. Keywords: Thinking Level,Van Hiele Theory, Reflective-Impulsive